Ang bago kong kalaro (my new playmate) - Garlitos, Rhandee (Chikiting books, 2013)
"In a flash,, Joko's world turned upside down. His family has found a betetr place to live so they must move to Sityo bagbaguin. Joko has to leave behind his friends and familiar surroundings. Meanshile, in Sityo Bagbaguin, Yunabelle tries to make friends with the animals around her because she has no one to play with. But they are too busy to play with her. Will Joko and Yunabelle ever find what will make them happy?In Ang bago kong kalaro,, we discover an unlikely story about unexpected joy that will touch the hearts of its readers."